Studying the Influence of Various Factors on the Properties of Thickers and Printing Compositions (Texas Journal of Engineering and Technology, 2022)
The article analyzes thickening ability of the developed composition in order to identify an integrated approach for stuffing fabric. The kinetic parameters of the influence of various factors on the physicochemical and rheological properties of the composition have been established. Particular attention is paid to the determination of the structural-mechanical, rheological properties of thickening polymer systems. The regularity of the interaction of the components in the aqueous medium, which are part of the polymer composition, is determined.